Layered Epistemic System in Sufi Exegesis: Reconstructing Symbolic Interpretation for Contemporary Qur'anic Studies - Siti Rohmah; Selvy Yuspitasari (Lembaga Bale Literasi, 2026)
Sufi exegesis (tafsir isyari) offers profound esoteric insights into the Qur'an, yet it frequently encounters academic skepticism due to perceived subjective biases and the absence of a systematized methodological framework. This study aims to reconstruct the methodology of symbolic interpretation in Sufi exegesis, bridging spiritual intuition with modern academic objectivity. Employing a qualitative library research design grounded in spiritual hermeneutics and historical-philosophical analysis, this research critically examines classical authoritative texts, including the works of Al-Tustari, Al-Qushayri, Al-Ghazali, and Ibn Arabi. The findings reveal that Sufi interpretation does not operate arbitrarily but functions through a novel